Biosensor for Aluminum(III) Based on α-Chymotrypsin Inhibition using a Disposable Screen-Printed Carbon Electrode and Acetyl-Tyrosine Ethyl Ester as Substrate - Barquero Quirós, Miriam (2015)
We report on a new amperometric assay for Al(III) ions based on the inhibition of α-chymotrypsin enzyme. The immobilization of the enzyme was performed on screen-printed carbon electrodes modified with gold nanoparticles and polyvinyl alcohol. N-acetyl-tyrosine ethyl ester, used as enzyme substrate, produces an oxidation amperometric signal, which at increasing aluminum concentration is diminished. The developed system has a detection limit of 1.5 ± 0.1 μM (n=7) for Al(III). The reproducibility of the method is 6.6% (n=5) and its repeatability is 8.2% (n=3). Main interferences at low concentration, include As(V), Cd(II), and Mo(VI) ions. The developed method was successfully applied to the determination of Al(III) in spiked white wine sample. Results agree with the certified value giving a value of percent recovery of 103 ± 4% (n=4).